2008
DOI: 10.1002/cbf.1478
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin affects the mobility and invasiveness of prostate cancer cells

Abstract: A significant proportion of prostate cancer patients treated with curative intent go on to develop advanced disease. At a fundamental biological level, very little is known about what makes the disease aggressive and metastatic. Observational pathology reports and experimental data suggest that epithelial-mesenchymal transition is involved in prostate cancer invasiveness. Here, we investigated vimentin expression of prostate cancer cells, and explored the potential mechanism of vimentin promoting prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 30 publications
8
80
0
3
Order By: Relevance
“…Vimentin is a mammalian structural cytoskeletal protein constituting type III mesenchymal filaments, and its elevated and aberrant expression correlates well with up-regulated cell invasion or migration both in the embryo and in malignancy [21] . Several studies have shown that vimentin could affect the invasion and motility of prostate cancer cells and is a promising marker for predicting aggressive and metastatic prostate cancer [22][23] . Consistent with their highly metastatic features, ARCaP M cells display higher expression of vimentin and other mesenchymal markers [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin is a mammalian structural cytoskeletal protein constituting type III mesenchymal filaments, and its elevated and aberrant expression correlates well with up-regulated cell invasion or migration both in the embryo and in malignancy [21] . Several studies have shown that vimentin could affect the invasion and motility of prostate cancer cells and is a promising marker for predicting aggressive and metastatic prostate cancer [22][23] . Consistent with their highly metastatic features, ARCaP M cells display higher expression of vimentin and other mesenchymal markers [14] .…”
Section: Discussionmentioning
confidence: 99%
“…This correlation has been demonstrated in migrating epithelial MCF10A cells, where vimentin is transiently and exclusively expressed in actively migrating cells at the wound edge, where it positively regulates migration (Gilles et al, 1999). Furthermore, fibroblasts of vimentin null mice exhibited defective wound healing due to reduced cell migration (Eckes et al, 1998(Eckes et al, , 2000 and in a pathological context, expression of vimentin promoted cell migration and invasion in breast, colon and prostate carcinomas (McInroy and MÀÀttĂ€, 2007;Zhao et al, 2008). The function of vimentin in cell migration and adhesion has also been reported in the transendothelial adhesion and extravasation of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, vimentin can also be expressed in epithelial cells undergoing epithelial-to-mesenchimal transition (EMT), 10 a reversible critical event in the progression toward cancer metastasis 11 characterized by reduced expression of epithelial markers such as E-cadherin and upregulation of mesenchymal markers such as N-cadherin and vimentin. 12,13 Accumulating evidences demonstrated that epithelial-mesenchymal transition has also been implicated in the onset of drug resistance and tumor relapses, representing an escape mechanism from apoptosis. 11 Vimentin expression is induced in invasive epithelial carcinoma cell lines [14][15][16] and is correlated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%